KEBIJAKAN DAN PERMASALAHAN AKSES PENDIDIKAN DASAR - Rizki Ananda; Rindani Nur Adma; Putri Anggraini; Putri Arifiana; Nursaiyana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Access to basic education is a cornerstone of human resource development and plays a vital role in a nation's progress. To ensure every child no matter their social, economic, or geographic background has a fair chance at receiving quality education, inclusive and equitable education policies are essential. However, in many countries, including Indonesia, several obstacles still limit access to basic education. These include uneven distribution of educational infrastructure, a shortage of qualified teachers, and economic and cultural barriers that hinder children's participation in school. This article explores the policies that have been introduced to improve access to basic education and examines the challenges that remain in achieving fair and equal education for all children. By understanding both the current policies and the ongoing issues, we can work towards finding effective solutions to expand educational access across different regions.